Bisphenol A substitutes and obesity: a review of the epidemiology and pathophysiology - Varghese, Shane V.; Hall, Julianne M. (Frontiers in Endocrinology, 2023)
The prevalence of obesity, a condition associated with increased health risks, has risen significantly over the past several decades. Although obesity develops from energy imbalance, its etiology involves a multitude of other factors. One of these factors are endocrine disruptors, or “obesogens”, when in reference to obesity. Bisphenol A (BPA), a known endocrine disruptor used in plastic materials, has recently been described as an environmental obesogen. Although BPA-free products are becoming more common now than in the past, concerns still remain about the obesogenic properties of the compounds that replace it, namely Bisphenol S (BPS), Bisphenol F (BPF), and Bisphenol AF (BPAF). The purpose of this review is to investigate the relationship between BPA substitutes and obesity. Literature on the relationship between BPA substitutes and obesity was identified through PubMed and Google Scholar, utilizing the search terms "BPA substitutes", "bisphenol analogues", "BPS", "BPF", "BPAF", "obesity", "obesogens", "adipogenesis", "PPARγ", and "adipocyte differentiation". Various population-based studies were assessed to gain a better understanding of the epidemiology, which revealed evidence that BPA substitutes may act as obesogens at the pathophysiological level. Additional studies were assessed to explore the potential mechanisms by which these compounds act as obesogens. For BPS, these mechanisms include Peroxisome proliferator‐activated receptor gamma (PPARγ) activation, potentiation of high‐fat diet induced weight‐gain, and stimulation of adipocyte hypertrophy and adipose depot composition. For BPF and BPAF, the evidence is more inconclusive. Given the current understanding of these compounds, there is sufficient concern about exposures. Thus, further research needs to be conducted on the relationship of BPA substitutes to obesity to inform on the potential public health measures that can be implemented to minimize exposures.